Association of genetic variances in ADRB1 and PPARGC1a with two-kilometre running time-trial performance in Australian Football League players: A preliminary study - Jacob, Y.; Anderton, R. S.; Cochrane Wilkie, J. L.; Rogalski, B.; Laws, S. M.; Jones, A.; Spiteri, T.; Hart, N. H. (Sports, 2021)
Genetic variants in the angiotensin-converting enzyme (ACE) (rs4343), alpha-actinin-3 (ACTN3) (rs1815739), adrenoceptor-beta-1 (ADRB1) (rs1801253), and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PPARGC1A) (rs8192678) genes have previously been associated with elite athletic performance. This study assessed the influence of polymorphisms in these candidate genes towards endurance test performance in 46 players from a single Australian Football League (AFL) team. Each player provided saliva buccal swab samples for DNA analysis and genotyping and were required to perform two independent two-kilometre running time-trials, six weeks apart. Linear mixed models were created to account for repeated measures over time and to determine whether player genotypes are associated with overall performance in the two-kilometre time-trial. The results showed that the ADRB1 Arg389Gly CC (p = 0.034) and PPARGC1A Gly482Ser GG (p = 0.031) genotypes were significantly associated with a faster two-kilometre time-trial. This is the first study to link genetic polymorphism to an assessment of endurance performance in Australian Football and provides justification for further exploratory or confirmatory studies.